The experience of parent/coaches in youth sport: A qualitative exploration of junior australian football - Elliot, S. K.; Drummond, M. (Journal of Amateur Sport, 2017)
There has been increasing academic interest in understanding the nature of parental involvement in youth sport. Much scholarly focus has illuminated both positive and negative forms of sport parenting from the perspectives of coaches, parents and youth participants. One less understood aspect however surrounds the potentially conflicting role of parents who coach their own children in youth sport. This is surprising given that many parents, especially fathers, demonstrate support by fulfilling essential roles such as team manager and team coach (Jeffery-Tosoni, Fraser-Thomas, & Baker, 2015). This paper emerges from an Australian study of 16 parent-coaches involved in Australian football. The original purpose of the study was to understand the nature of the sport parenting role in youth sport in Australia. A number of pertinent themes were constructed surrounding the contemporary experiences of parent-coaches who coach their own children, and how coaching is subsequently justified. The findings illustrate how concerns of favouritism impact how parent-coaches interact with their child in contrast to the rest of the team, encouraging nuances of `negative` parenting toward their own children under the guise of being the coach. Examples of this include demonstrating deliberate criticism at training and matches and overlooking their child in awarding encouragement awards after each weekly match. Significantly, parent-coaches justify these behaviours in attempting to fulfil the dual role of parent and team coach. We argue that this can be potentially problematic for some parent and child relationships and have a reinforcing influence on how other parent-coaches negotiate being a parent and coach.